The Effect of Work Ability and Work Motivation on the Performance of the State Civil Apparatus at Regional Inspectorates Sidrap District - Andi Pattarani; Nur Ilmiah Rivai, Herlina Erawati (International Journal of Management Progress, 2021)
This study aims to determine whether the ability and work motivation affect the performance of the State Civil Apparatus at the Regional Inspectorate of Sidrap Regency. The data collection techniques in this study were observation and questionnaires. The results showed that from the results of statistical data analysis and the results of Ftable where, Fcount (354.925 ) > Ftable (3.17) and a significance value of 0.000 < 0.05, this proves that together or simultaneously there is a significant effect of ability and work motivation . While the results of the t test or partial, the test results obtained the t value for the X1 variable (workability) obtained the Sig value of 0.000 < 0.05 and the tcount (8.041) > ttable value (2.00665) indicates that Ho is rejected and Ha is accepted means that there is a partially significant effect between work ability (X1) on performance (Y). Variable X2 (work motivation) obtained Sig value 0.000 < 0.05 and tcount value (6.235) > ttable value (2.00665) indicates that Ho is rejected and Ha is accepted meaning that there is a significant influence between work motivation (X2) on performance (Y). the value of R Square is 0.932 which indicates that ability (X1) and motivation (X2) simultaneously affect the performance (Y) of the State Civil Apparatus at the Regional Inspectorate of Sidrap Regency by 0.932 or (93.2%).